问题 解答题
3
4
+
5
6
-
7
8
6
7
-(
11
14
-
1
2
7
8
-
4
5
+
9
8
-
1
5
7
12
+(
5
12
-
3
4
6-
3
11
-
8
11
5
9
+
9
8
+
4
9
+
7
8
答案

解;(1)

3
4
+
5
6
-
7
8

=

18
24
+
20
24
-
21
24

=

17
24

(2)

6
7
-(
11
14
-
1
2
),

=

6
7
-
2
7

=

4
7

(3)

7
8
-
4
5
+
9
8
-
1
5

=(

7
8
+
9
8
)-(
4
5
+
1
5
),

=2-1,

=1;

(4)

7
12
+(
5
12
-
3
4
),

=

7
12
+
5
12
-
3
4

=1-

3
4

=

1
4

(5)6-

3
11
-
8
11

=6-(

3
11
+
8
11
),

=6-1,

=5;

(6)

5
9
+
9
8
+
4
9
+
7
8

=(

5
9
+
4
9
)+(
9
8
+
7
8
),

=1+2,

=3.

单项选择题
问答题 简答题